A Geographical Approach to Water Resource Mapping for Atlases - Leonid M. Korytny; Olga V. Gagarinova; Elena A. Ilyicheva; Natalya V. Kichigina (Geography, Environment, Sustainability)
We examine water resource mapping as an important component of the geographical approach in land hydrology and in the water sector which serves to assist considerably in dealing with water problems and water resource management. We suggest that seven groups of water resource maps be distinguished: introductory maps, maps of formation of surface and subsurface water regimes, maps of assessments of water resource potential, maps of water management, maps of anthropogenic impacts on water, maps of hazardous hydrological phenomena and maps of water protection measures. Characteristic properties water resource mapping for atlas products are identified using a case study of territory surrounding Lake Baikal as a site of global significance. We compiled an inventory of water resource themes covered by various atlases of the Baikal region and determined gaps relating to economic aspects of water and to maps on water protection. Limitations of the traditional isoline method in geographical water resource mapping are shown. At hillslope level where atmospheric precipitation transforms to surface runoff further to stream flow, it is recommended that the indication localization method be used, which is based on interdependencies of components of the geosystem. Water runoff mapping at the regional level in the hydrographic network uses the technique of long-channel (epure) mapping based on tools of structural hydrographic and Horton-Strahler classification. A technique of regionalization is described for flood hazards, water protection and recreation zoning of Baikal’s shores as well as cartographic modeling of processes in the Selenga river delta.